The Anchoring of Inflation Expectations in the Short and in the Long Run - Dieter Nautz; Aleksei Netsunajew; Till Strohsal (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We introduce structural VAR analysis as a tool for investigating the anchoring of inflation expectations. We show that U.S. consumers' inflation expectations are anchored in the long run because macro-news shocks are long-run neutral for long-term inflation expectations. The identification of structural shocks helps to explain why inflation expectations deviate from the central bank's target.
Keywords: E31; E52; E58; 330